A relationship between brainstem auditory evoked potential and vagal control of heart rate in adult women - Silva, Ariany G. [UNESP]; Frizzo, Ana Claúdia F. [UNESP]; Chagas, Eduardo F. B. [UNESP]; Garner, David M.; Raimundo, Rodrigo D.; De Alcantara Sousa, Luiz Vinicius; Valenti, Vitor E. [UNESP] (The Nencki Institute of Experimental Biology, Polish Academy of Sciences, 2018)
Numerous studies have investigated the connection between autonomic control of heart rate (HR) and auditory stimulus. Yet, the literature lacks evidence of a close association between auditory brainstem processing and HR autonomic control. We aimed to evaluate and verify the relationship between auditory brainstem response (ABR) and HR variability (HRV) in healthy women. Forty-six healthy female subjects, between the ages of 18 and 30 years old participated in the study. They were subjected to an audiometry examination, followed by rest for 10 minutes for HR recording. Next, ABR evaluation was completed discretely in both ears, with I, III and V wave components. Linear regression revealed that the root-mean square of differences between adjacent normal RR intervals (RMSSD) and the triangular interpolation of RR interval (TINN) exhibited a significant association with Wave I in the right ear. These variables contributed to 28.2% (R 2 ) of Wave I. In conclusion, there was a significant interaction between the autonomic control of HR and auditory processing in the right ear, suggesting that vagal tone interacts with the cochlear nerve.
Keywords: Autonomic nervous system; Cardiovascular system; Hearing; Language and hearing sciences; Neurophysiology; Speech